TB control in humanitarian emergencies: Lessons from the Syria displacement crisis. (February 2019) - Boyd, Andrew T.; Cookson, Susan T.
Abstract: The TB care for communities in emergency contexts satellite session at the 2017 48th Union World Conference on Lung Health discussed the impact of the Syrian displacement crisis on regional tuberculosis (TB) control. At the session, representatives of the affected countries and of international organizations reviewed the epidemiologic impact of Syrian displacement on regional TB control, as well as challenges and successes seen in TB control during this displacement. This discussion offered several lessons for TB control in other humanitarian emergencies. TB control in humanitarian emergencies requires increasing awareness of TB symptoms and services among healthcare workers and the affected populations. It also requires performing standardized symptom screening at borders or registration, while leveraging more widely available radiographic and diagnostic tools to find cases in high-burden settings that may be missed using symptom screening alone. Additionally, treatment completion rates can be maintained and improved through dedication of sufficient resources and innovative strategies to keep mobile populations on treatment. Finally, sustained commitment, including funding, from the international humanitarian community is necessary to improve TB control, and ultimately end TB, both in the Syria crisis and other humanitarian emergencies worldwide.